Feedstock-Induced Changes in the Physicochemical Characteristics of Biochars Produced from Different Types of Pecan Wastes - Zhang, Miaomiao; Peng, Fangren; Yu, Jinping; Liu, Zhuangzhuang (Forests, 2024)
Large amounts of residues are generated in pecan cultivation processes. Biochar is an environmentally friendly way to utilize residues but attempts to prepare and apply biochar with pecan residues are rare. In this study, six types of biochars were produced from pecan branches, trunks, roots, nutshells, husks, and leaves under pyrolysis, and their physicochemical properties were compared to assess their application perspective in environmental and agricultural fields. The yields of six pecan biochars were 32.1%–45.9%, with the highest yield for husk biochar (HB) (45.9%). Among the pecan biochars, trunk biochar (TB) and root biochar (RB) had much larger specific surface areas. Branch biochar (BB), TB, and RB presented tubular structures with elliptical pores, while nutshell biochar (NSB), HB, and leaf biochar (LB) appeared flaky or as clustered structures with relatively rougher outer surfaces and irregular pores. The functional group types of pecan biochars were generally similar, but the intensities of the peak near 2900 cm−1 in BB were obviously higher than those of the other biochars. RB and LB contained significantly more ash and volatile than those of the other pecan biochars, with the highest fixed carbon content being found in NSB (70.1%). All of the pecan biochars were alkaline (7.90–9.87), and HB, LB, and NSB had significantly higher pH values than those of the other biochars. Elemental analysis indicated that RB, NSB, and LB had higher carbon levels (more than 70%) with lower O/C ratios (no more than 0.2). HB possessed a relatively high content of nitrogen, potassium, magnesium; the phosphorus content was highest in NSB; LB had the highest calcium content. The results of principal component analysis showed that BB, LB, and NSB were clustered in the same quadrant with relatively close relationships. The results of this study can guide the utilization of pecan wastes and their application as biochar in different fields.